2011
DOI: 10.1111/j.1600-048x.2010.05113.x
|View full text |Cite
|
Sign up to set email alerts
|

From preen secretions to plumage: the chemical trajectory of blue petrels' Halobaena caerulea social scent

Abstract: Petrel seabirds heavily rely on their olfactory sense and are thus appropriate models for the study of avian chemical communication. The uropygial secretions of blue petrels Halobaena caerulea, for instance, have been shown to encapsulate elaborate sociochemical information including species, gender and identity. Yet, it is the plumage, and not preening secretions per se, which acts as the final substrate of avian scents. Importantly, the chemical relationship between secretions from the uropygial gland, locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 53 publications
(96 reference statements)
0
39
1
Order By: Relevance
“…Results show that mice were exploring the unknown odor significantly more often than expected by chance (Celerier et al, 2011), confirming that blue petrels have an individual odor (Mardon et al, 2010; 2011b), and showing that mice were able to perceive and discriminate this perfumed individuality. But mice also seemed able to identify kin-related individual birds.…”
Section: Importance Of Chemosignals In Successive Reproductive Stagesmentioning
confidence: 56%
See 1 more Smart Citation
“…Results show that mice were exploring the unknown odor significantly more often than expected by chance (Celerier et al, 2011), confirming that blue petrels have an individual odor (Mardon et al, 2010; 2011b), and showing that mice were able to perceive and discriminate this perfumed individuality. But mice also seemed able to identify kin-related individual birds.…”
Section: Importance Of Chemosignals In Successive Reproductive Stagesmentioning
confidence: 56%
“…Chemical cues have been shown to play a role in both species and sex recognitions in birds. The comparisons of the chromatographic profiles of chemical compounds coming from different bird species, populations and sexes have shown that all these levels of organization can be reliably identified (Bonadonna et al, 2007; Jacob et al, 1979; Leclaire et al, 2011; Mardon et al, 2010; 2011b; Whittaker et al, 2010; Zhang et al, 2013). For example, two subspecies of sharewaters, the Atlantic and the Mediterranean Cory’s sharewaters, have recently been shown to differ in their chemical profiles (Gabirot M., Raux L., Dell’Ariccia G., Bried J., Gonzales-Solis J., Buatois B., Crochet P.A., Bonadonna, F., unpublished data).…”
Section: Importance Of Chemosignals In Successive Reproductive Stagesmentioning
confidence: 99%
“…The uropygial gland lipids, in the blue petrel, may also contain microbes that could modify these odour components to accentuate individual odours. Moreover, degradation of the gland components, which may be attributed to microbial breakdown, has been shown on the feathers of blue petrels [58]. Consequently, if the uropygial gland or feather microflora is determined by the MHC profile, it could contribute to the personal odour signature.…”
Section: Discussionmentioning
confidence: 99%
“…More precisely, a detailed chemical examination of the uropygial secretions and feathers of Antarctic prions (Pachyptila desolata) and blue petrels (by gas chromatography) has shown that these two petrel species exhibit critical socio-ecological information, such as species, gender and individual identity, which could be involved in olfactory behaviours observed in the field (i.e. individual recognition, self-odour avoidance) [16][17][18].…”
Section: Introductionmentioning
confidence: 99%